Survey and Detection of Pectobacterium atrosepticum in Major Potato-Growing Areas in Central Java Province, Indonesia - Ismiyatuningsih Ismiyatuningsih; Tri Joko; Sedyo Hartono (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
Potato (Solanum tuberosum) is a seasonal shrub-tuber crop originated from sub-tropical area. Soft-rot is one of the most important diseases of potato. It can be caused by Pectobactorium atrosepticum, a pathogen within a status of quarantine plant pest A1 type I in Indonesia. The objective of this study was to know the incidence of potato soft rot disease and to detect P. atrosepticum in major potato-growing areas in Central Java Province by applying the serology method using DAS-ELISA technique. Survey of soft rot disease was carried out in some regencies in Central Java Province, i.e. Magelang, Banjarnegara, Wonosobo and Karanganyar. The field survey of potato plant in all the regencies indicated symptoms of stem rot which was black in color (blackleg) and foul-smelling, with disease incidence of about 10–90%. The laboratory testing showed that by applying DAS-ELISA method, P. atrosepticum was detected in samples collected from Pandean and Bagongan villages, district of Ngablak,Regency of Magelang, Central Java Province.